Factors Predicting Self-Management Among Older Persons with Type 2 Diabetes Mellitus - Phanlek, Netnapa; Suwankruhasn, Nattaya; Chintanawat , Rojanee (Nursing Journal CMU, 2022)
Appropriate self-management is important for helping older persons with type 2 diabetes mellitus maintain their blood sugar at a normal level, thereby reducing the disease’s complications. This descriptive predictive study aimed to examine the level of health literacy, self-efficacy, social support, and self-management of older persons with type 2 diabetes mellitus, and to investigate the predictive ability of health literacy, self-efficacy, and social support on their self-management. The sample consisted of 120 older persons with type 2 diabetes mellitus who were treated at a Health Promoting Hospital. The instruments for data collection were the Demographic Data Questionnaire, the Health Literacy of Older Persons with Type 2 Diabetes Mellitus Questionnaire, the Self-Efficacy Questionnaire, the Social Support in Older Persons with Type 2 Diabetes Mellitus Questionnaire, and the Self-Management of Older Persons with Type 2 Diabetes Mellitus Questionnaire. Data were analyzed using descriptive statistics and stepwise regression statistics. The results showed that the participants had a moderate level of health literacy ( = 40.92, SD = 5.65), a moderate level of self-efficacy ( = 225.37, SD = 11.20), a high level of social support (= 53.32, SD = 5.05), and a high level of overall self-management ( = 54.34, SD = 4.58). Health literacy, self-efficacy, and social support could together predict self-management of older persons with type 2 diabetes mellitus at 26.50%, with self-efficacy having the strongest predicting ability (β = .433, p < .001), followed by health literacy (β = .195, p < .05), and social support (β = .164, p < .05). Nurses or health care providers should encourage older people with type 2 diabetes to have self-efficacy and health literacy, and to receive social support for managing blood sugar levels.